Comparison of lung clearance index determined by washout of N2 and SF6 in infants and preschool children with cystic fibrosis - Stahl, Mirjam; Joachim, Cornelia; Wielpütz, Mark Oliver; Mall, Marcus A. (Journal of cystic fibrosis, 2019)
BACKGROUND: Multiple-breath washout (MBW) has been shown to detect early impairment of lung function in children with cystic fibrosis (CF). Nitrogen (N2) or sulfur hexafluoride (SF6) can be used as tracer gas for MBW. Recent data indicated higher lung clearance index (LCI) values measured with N2-MBW than concurrent SF6-MBW in older children and adults, however, a comparison in infants and younger children, as well as to other outcome measures of CF lung disease is pending. - METHODS: N2- and SF6-MBW were performed consecutively in 31 sedated infants and preschool children with CF (mean age, 2.3±0.8years) and 20 controls (mean age, 2.3±1.1years) using the Exhalyzer D system. Children with CF also underwent chest magnetic resonance imaging (MRI). - RESULTS: Mean difference (95% CI) in LCI between N2- and SF6-MBW was 1.1±0.4 (0.9 to 1.3) in controls and 2.1±1.9 (1.4 to 2.8) in CF. Agreement between N2- and SF6-LCI was poor in children with CF. N2-LCI and SF6-LCI correlated with MRI, however N2-LCI showed a higher concordance with MRI than SF6-LCI. The absolute difference between N2- and SF6-LCI values increased with the severity of CF lung disease as determined by MRI scores. - CONCLUSION: N2-LCI values were higher than SF6-LCI values in infants and preschool children with CF and controls. Better concordance of N2-LCI than SF6-LCI with chest MRI scores point towards of a higher sensitivity of N2-LCI to detect early lung disease in children with CF.